PEMBERDAYAAN KELOMPOK WANITA TANI DESA KARANGTURI MELALUI PELATIHAN TEKNIK BUDIDAYA TANAMAN SAYURAN SECARA HIDROPONIK - Muhammad Safrudin Musthofa; Iola Mieliki; Diana Putri; Dimas Dharma Gautama; Dionisius Samudra; Dyah Ayu Ramadhani; Eddy Bagoes Prastyo; Elysa Indriyani; Muhammad Ivan Rizki; Eksa Rusdiyana (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Community empowerment is one of the foundations for the development of a civilization and the progress of society. quality based on attitudes, knowledge and skills becomes an indicator of the success of an empowerment. The community service activities in this article aim to introduce and practice hydroponic plant cultivation techniques to attract the interest of members of the Women Farmers Group (KWT) in Karangturi Village to plant vegetable crops around the house. The implementation method is carried out with a group approach through demonstration techniques. The results of the activity showed an increase in the knowledge of the participants about hydroponic cultivation techniques. In addition, increasing skills in hydroponic cultivation techniques both in nutrition management, nurseries, as well as technical treatment and waste treatment.